Hubungan Minat Baca dengan Prestasi Belajar Bahasa Indonesia Siswa Kelas V Sekolah Dasar Torsina III Singkawang - Lala, Selia; Safrihady, Safrihady; Mulyani, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstract. This study aims to determine the relationship between reading interest and Indonesian language learning achievement of fifth grade students at SD Torsina III Singkawang. The type of research used is quantitative with a correlational research design. Data collection techniques using questionnaires and documentary studies. Data were analyzed using a correlation test with a level of 0.05 and looking for variable contributions with the determinant coefficient formula. The results of the study showed that there was a significant relationship (correlation) between reading interest and learning achievement. With a correlation coefficient of 0.454, which means it has a moderate relationship based on the correlation level. Reading interest has a contribution of 21%. The implications of this study indicate that efforts are needed to increase students' reading interest in order to have a positive impact on learning achievement.Keywords: Relationship; reading interest; learning achievement; Indonesian.